2012
DOI: 10.1002/lary.23643
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of cutanplast nasal packing after endoscopic sinus surgery: A prospective, randomized, controlled trial

Abstract: Cutanplast nasal pack results in significantly less pain and less bleeding compared to Merocel pack.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
43
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 26 publications
(63 reference statements)
4
43
0
2
Order By: Relevance
“…The same four studies [8,11,13,15] also reported the sex distribution of the participants, with the ratio of males ranging from 54 to 67%. For the absorbable nasal packing materials, MeroGel ® was used in two studies [8,12], while Cutanplast [15], carboxymethylated cellulose (CMC) foam [13], and NasoPore [11] were used in the other three studies, respectively. For nonabsorbable nasal packing material, Merocel was used in three studies [8,11,15], polyvinyl alcohol sponges [12], and routine nasal packing (coton gauze placed in a latex glove inger) [13] were used in the remaining two studies respectively.…”
Section: Search Of Literaturementioning
confidence: 93%
See 4 more Smart Citations
“…The same four studies [8,11,13,15] also reported the sex distribution of the participants, with the ratio of males ranging from 54 to 67%. For the absorbable nasal packing materials, MeroGel ® was used in two studies [8,12], while Cutanplast [15], carboxymethylated cellulose (CMC) foam [13], and NasoPore [11] were used in the other three studies, respectively. For nonabsorbable nasal packing material, Merocel was used in three studies [8,11,15], polyvinyl alcohol sponges [12], and routine nasal packing (coton gauze placed in a latex glove inger) [13] were used in the remaining two studies respectively.…”
Section: Search Of Literaturementioning
confidence: 93%
“…Table 1 summarized the systematic review, which included the studies characteristics [8,[11][12][13]15]. A total of 241 nasal cavities were treated in each group for all studies combined and the number of nasal cavities treated in each study ranged from 30 to 100.…”
Section: Search Of Literaturementioning
confidence: 99%
See 3 more Smart Citations